De-novo portal vein thrombosis in liver cirrhosis: risk factors and correlation with the Model for End-stage Liver Disease scoring system. Issue 5 (May 2015) - Abdel-Razik, Ahmed; Mousa, Nasser; Elhelaly, Rania; Tawfik, Ahmed
Abstract : Background and objectives: Portal vein thrombosis (PVT) is a potential lethal complication in late liver cirrhosis. There is a lack of knowledge of the clinical features and risk factors of PVT. We aimed to investigate the clinical and radiological characteristics, and biochemical markers of cirrhotic patients to determine the high-risk individuals for PVT attending our center. Patients and methods: Of 426 cirrhotic patients, only 120 consecutive patients were included. Clinical, biochemical, immunological, Model for End-stage Liver Disease (MELD) score, portal vein patency, and flow velocity were measured in all patients at baseline and every 6 months thereafter. Variables that could predict the development of PVT within 1 year were identified by multiple logistic regression. Results: Only 95 patients completed the study; PVT was found in 17 (17.9%) patients. PVT was observed mainly in the portal trunk, superior mesenteric vein, and splenic vein. Univariate analysis showed that diabetes mellitus, lower levels of hemoglobin, platelet counts, and portal vein flow velocity as well as increased MELD scores, platelet indices, portal vein diameter, and splenic thickness were associated with PVT patients than in non-PVT patients (all P <0.01). Conclusion: The incidence of PVT was 17.9%. PVT occurred mainly in the portal vein trunk, superior mesenteric vein, and splenic vein. Diabetes mellitus, lower levels of hemoglobin, platelet count and portal vein flow velocity as well as increased MELD score, platelet indices, portal vein diameter, and splenic thickening were associated with PVT. Splenic thickening, marked reduced of mean portal flow velocity, and diabetes mellitus may be risk factors for PVT.